立式车床降低噪声的实验研究 - 邓效忠; 吴云斌; 兰新哲 (Jixie chuandong)
In this paper, the noise of vertical lathe with double spindles was researched by noise measurement and noise spectrum analysis. According to the result, two gears are found and re-designed, which have main contribution for system noise, the noise of this vertical lathe has been reduced for 3 dB.（A）